Spectral pigment indices of phytoplankton in different water objects of Belarus - Smolskaya, Volha S.; Zhukava, Hanna A. (Journal of the Belarusian State University. Ecology, 2018)
The paper presents the results of studying the absorption spectra of phytoplankton pigments in various types of objects, such as the large river, small rivers and fish farm ponds). Different pigment indices Е450/Е480, Е480/Е664, Е430/Е664, Е480/Е665, Е664/Е720, Е430/Е720, Е412/Е720, Е530/Е720, Е430/Е530, Е664/Е530, Е412/Е664 are estimated that characterize the water quality and physiological state of phytoplankton. The optical density of the extract was measured in the range of 350 nm to 800 nm in 1 nm steps, 90 % acetone was used as the solvent. It is shown that the water sample is suitable for the calculation of pigment indices and chlorophyll content if the spectrum has clearly expressed absorption maxima located in the red and blue regions of the spectrum at about 663–665 nm and 430 nm. It was found that there is no statistically significant difference between light absorption at 720 nm and 750 nm, which allows a shorter portion of the spectrum to be recorded without loss of relevant information.
Keywords: pigment indices; chlorophyll; photo pigments; photosynthesis; absorption spectrum; wavelength; water objects